مكملات مقاصد الشريعة وتطبيقاتها في المعاملات المالية المعاصرة : دراسة تأصيلية تحليلية - غرابلي، رزق محمد غازي رشدي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research represents an applied study of usul al-fiqh (principles of Islamic jurisprudence) concerning the supplementary aspects of the objectives of Shari'ah. The researcher has delved on establishing the basic principles in relation to this part of Islamic jurisprudence by gathering the relevant materials and subjecting them to a proper analysis. The applied part focuses on issues of contemporary financial transactions, as this has become one of the important topics in juristic studies, attracting plenty of interest in line with the immense developments in the areas of finance, economics and technology of today. The researcher focuses on the problems that emanate from the lack of proper juristic operationalization concerning the supplements of the objectives of Sharī'ah and loose consideration thereof within the context of contemporary ijtihad, which has led to shaky contextualization of the issues at hand and in turn, flawed rulings. On the other hand, this research traces the various levels of consideration for the supplements of the objectives of Shari'ah from the time of the rightly-guided caliphs and the companions of the Messenger of Allah, through the companions of the companions, the pre-eminent scholars and others who are capable of exercising ijtihad until contemporary times. The importance of this study is to open the door for contemporary jurists and those exercising ijtihad to properly establish the consideration of the supplements of the objectives of Shari'ah in their edicts and rulings, especially in our era in which issues are multifaceted and on top of that, become more complicated with non-specialized people coming up with edicts of their own. In order to properly realize the objectives of this research, the researcher uses the inductive method of gathering the relevant materials in a scientifically consistent manner, and the analytical method to make appropriate interpretations. The research arrived at some significant findings, among which is that the consideration for the supplements of the objectives of Shari'ah was in fact observable in the conceptualization of issues and the derivation of rulings among the pre-eminent scholars of the past and the fiqh academies throughout history. Anything that deviated from that had, in fact, an element of either loose reasoning or overly rigid conceptualization, which are both shunned by the Shari'ah. Consideration for the supplements of the objectives of Shari'ah plays an important role in legislating for financial issues, especially in preferring some opinions over the others when there are conflicting opinions and disputes. The effects of that can be seen in the outcomes of the financial products introduced to the market. In light of the above, this research can therefore be considered to be the first of its kind in giving a solid theoretical framework that also integrates the supplementary aspects of the objectives of Shari'ah and this is clearly demonstrated through a host of issues that such supplements have had their impact on ijtihad.